Gender Transformative Socio-Technical Innovation Bundles (GTSTIBs) scaling workshop report - Embu County, Kenya - Lutomia, Cosmas Kweyu; Nyamolo, Victor; Muriithi, Catherine; Rono, Bernard; Kagete, Eliud; Amboga, Seth Chasimba; Nchanji, Eileen (2025)
This workshop brought together county officers, Kenya Agricultural & Livestock Research Organisation, CARITAS, NGOs, nutrition experts from the County Government, Alliance of Bioversity International and CIAT, and farmer leaders to plan how to scale gender-transformative socio-technical innovation bundles (GTSTIBs). Participants reviewed baseline/endline evidence showing early gains in empowerment, productivity, resilience and diets, reflected on farmer experiences, and co-created a practical scaling roadmap. Priorities included integrating GTSTIBs into extension and county plans, strengthening finance linkages, and deliberately including women, youth and persons with disabilities. The workshop also delivered participatory nutrition training and agreed next steps on monitoring, institutional anchoring and follow-up actions across sub-counties.